Marketing Strategy Analysis to Increase Consumer Purchasing Decisions at the Sampoerna Retail Community (SRC) Nesya Store in Muara Jaya Village, Sukadana District - Anggi Yuliani; Robi Santoso; Diki Angga Hendrawan (Indonesian Journal of Entrepreneurship and Startups, 2026)
This research examines how marketing strategy shapes consumer purchase decisions at the Sampoerna Retail Community (SRC) Nesya outlet in Muara Jaya Village, Sukadana District. Growing rivalry between conventional shops and modern retail formats pushes small business owners to design marketing approaches capable of keeping their customers loyal, and this need forms the background of the study. A descriptive qualitative design guided the investigation. Informants the store owner, staff members, and shoppers were chosen through purposive sampling. Interviews, field observation, and documentation supplied the data, which were then processed through reduction, display, and conclusion-drawing stages. Findings show that the four marketing-mix elements applied at SRC Nesya product, price, promotion, and service jointly contribute to stronger purchase decisions among consumers. Shoppers reported being drawn in mainly by product variety, prices matched to local buying power, quick and friendly service, and face-to-face promotion. Overall, the study concludes that well-designed marketing strategy can lift consumer purchase decisions while helping traditional retailers stay competitive as modern retail continues to expand